2021
DOI: 10.3389/fphar.2021.724670
|View full text |Cite
|
Sign up to set email alerts
|

Danlou Tablets Inhibit Atherosclerosis in Apolipoprotein E-Deficient Mice by Inducing Macrophage Autophagy: The Role of the PI3K-Akt-mTOR Pathway

Abstract: Atherosclerosis (AS) is a type of chronic vascular disease, and its etiology is not yet fully understood. AS is characterized by lipid deposition, atherosclerotic plaque formation, vascular stenosis or even complete blockage of the blood vessel wall. Clinical studies have shown that Danlou tablets (DLTs) can improve the heart function, quality of life, and prognosis of patients with coronary heart disease and myocardial infarction. However, its mechanism of action remains unknown. Our study revealed that DLTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The PI3K/AKT/mTOR signaling pathway is a classical autophagic pathway. Meanwhile, it was also found that Danlou tablets (DLTs) can promote autophagy in macrophage by inhibiting this signaling pathway, thereby reducing FCs formation and improving AS ( Liu et al, 2021 ). Despite lots of studies on the role of autophagy in anti-AS, those on the specific mechanism of autophagy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signaling pathway is a classical autophagic pathway. Meanwhile, it was also found that Danlou tablets (DLTs) can promote autophagy in macrophage by inhibiting this signaling pathway, thereby reducing FCs formation and improving AS ( Liu et al, 2021 ). Despite lots of studies on the role of autophagy in anti-AS, those on the specific mechanism of autophagy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…68,69 However, there are currently no available data showing its effect on the inhibition of atherosclerosis progression. 70 Moreover, Torin1 inhibits mTORC2, which is involved in insulin signaling. Thus, long-term drug use of the drug has serious adverse effects, such as insulin resistance and glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, macrophages promote and maintain inflammatory response and promote the development of AS in patients with psoriasis. In addition, macrophages not only promote the expression of inflammatory factors in patients with psoriasis, but also increase the formation of cholesterol crystals and lipid uptake, affect cholesterol excretion, and further promote the occurrence of AS ( 45 , 48 , 49 ).…”
Section: Immunity and Psoriasis - Atherosclerosis Are Closely Relatedmentioning
confidence: 99%